6-exo-trig Michael addition-lactonizations for catalytic enantioselective chromenone synthesis. Issue 17 (30th January 2017) - Neyyappadath, Rifahath M.; Cordes, David B.; Slawin, Alexandra M. Z.; Smith, Andrew D.
Abstract : The catalytic enantioselective 6- exo -trig Michael addition-lactonization of enone-acid substrates to form cis -chromenones with high diastereo- and enantiocontrol was developed using the commercially available isothiourea tetramisole. Abstract : The catalytic enantioselective 6- exo -trig Michael addition-lactonization of enone-acid substrates to form cis -chromenones with high diastereo- and enantiocontrol was developed using the commercially available isothiourea tetramisole. An acidic workup proved necessary to minimize product epimerization and maximize product er, providing cis -chromenones in excellent yield, and with excellent diastereo- and enantioselectivity.